Hepatocellular Carcinoma: Consensus Recommendations of the National Cancer Institute Clinical Trials Planning Meeting - Thomas, Melanie B. (American Society of Clinical Oncology, 2010)
Hepatocelluar carcinoma (HCC) is the most common primary malignancy of the liver in adults and the third most common cause of cancer death worldwide. The incidence of HCC in the United States is rising steadily because of the prevalence of hepatitis C viral infection and other causes of hepatic cirrhosis. The majority of patients have underlying hepatic dysfunction, which complicates patient management and the search for safe and effective therapies. The Clinical Trials Planning Meeting (CTPM) in HCC was convened by the National Cancer Institute's Gastrointestinal Cancer Steering Committee to identify the key knowledge gaps in HCC and define clinical research priorities. The CTPM structured its review according to current evidence-based treatment modalities in HCC and prioritized the recommendations on the basis of the patient populations representing the greatest unmet medical need.